Outcomes and xerostomia after postoperative radiotherapy for oral and oropharyngeal carcinoma. Issue 10 (13th January 2014) - Wang, Zhong‐He; Yan, Chao; Zhang, Zhi‐Yuan; Zhang, Chen‐Ping; Hu, Hai‐Sheng; Tu, Wen‐Yong; Kirwan, Jessica; Mendenhall, William M.
Abstract Background We compared outcomes and xerostomia grade after postoperative intensity‐modulated radiation therapy (IMRT) and conventional radiotherapy (RT) in patients with oral and oropharyngeal carcinoma. Methods Eighty‐eight patients with oral cavity (n = 77) and oropharyngeal (n = 11) carcinoma underwent postoperative IMRT (n = 44) or conventional RT (n = 44). Outcomes, failure patterns, volume, doses, salivary gland V30, and xerostomia grade were evaluated. The median follow‐up was 53 months (range, 48–58 months). The median interval from surgery to RT was 4 weeks (range, 3–6 weeks). Results Twenty‐one patients (7 and 14 for the IMRT and conventional RT groups, respectively) experienced local‐regional failure. For the IMRT group, all 7 local‐regional failures occurred in the high‐dose target volumes. For the conventional RT group, there were 12 in‐field failures, 1 at the margin, and 1 out‐of‐field. Nine patients experienced distant failure (5 and 4 for the IMRT and conventional RT groups, respectively). The 4‐year local‐regional control, disease‐free survival (DFS), overall survival (OS), and distant‐metastasis rates for the IMRT and conventional RT groups were 84.1% versus 68.2% (p = .055), 68.2% versus 52.3% (p = .091), 70.5% versus 56.8% (p = .124), and 11.4% versus 9.1% (p = .927), respectively. Xerostomia grade after RT was lower for IMRT compared to conventional RT (p < .001). Conclusion Postoperative IMRT for oral and oropharyngeal carcinoma significantly improves mean dose, salivary gland V30, and xerostomia grade when compared to conventional RT. The predominant failure pattern was local. No differences were found in survival outcomes between both groups. There was a marginal difference in local‐regional control. © 2014 Wiley Periodicals, Inc. Head Neck, 36: 1467–1473, 2014